(untitled) (Vegueta: Anuario de la Facultad de Geografía e Historia, 2014)
En este trabajo formulamos como hipótesis de partida que Canarias, como frontera meridional de Europa, en un contexto de creciente internacionalización, tiene en los mercados africanos una gran baza histórica que desempeñar. Dado el interés general que este asunto suscita entre las ciencias sociales, se requiere abordarlo desde el análisis geográfico. Para cumplimentar este estudio se emplearon las estadísticas que ofrecen organismos oficiales como el Instituto Nacional de Estadística, Instituto Canario de Estadística, Agencia Estatal de la Administración Tributaria, Instituto de Comercio Exterior y entidades internacionales como la Conferencia de las Naciones Unidas para el Comercio y el Desarrollo (UNCTAD) y la Organización Mundial del Comercio (OCM). In this work we formulate the hypothesis that the Canary Islands, as Europe’s southern border, must develop an important role in African markets, in a context of increasing internationalization. Because of the general interest in this issue within the social sciences, to address it from the geographic analysis is required. This study is based, on the one hand, on statistics provided by Spanish government agencies such as the National Statistics Institute, the Canary Institute of Statistics, the State Tax Administration Agency and the Institute of Foreign Trade and, on the other hand, by international entities such as the United Nations Conference for Trade and Development (UNCTAD) and the World Trade Organization (WTO).